Development and validation of a highly sensitive gradient chiral separation of pramipexole in human plasma by LC–MS/MS. (May 2017) - Michi, Marco; Breda, Massimo; Belardi, Justin Keane; Dworetzky, Steven; Solazzo, Lara
Aim: Development of a high-sensitivity chiral LC–MS/MS method was required to evaluate a combination of pramipexole ( S -PPX) and its enantiomer dexpramipexole ( R -PPX) in a proposed clinical trial. The previously available methods suffered from low sensitivity for the ( S )-enantiomer in the presence of the more abundant ( R )-enantiomer. Based on the projected dosing regimen in the clinical trial, a 5000-fold improvement in sensitivity was required for the ( S )-enantiomer.Methodology : Spiked human plasma samples were extracted by liquid–liquid extraction using ethyl acetate and injected onto a CHIRALPAK ID column under pH gradient conditions.Conclusion: An improved analytical method was developed and validated with a final LLQ for ( S )-PPX of 0.1 ng/ml in the presence of 2000 ng/ml of ( R )-PPX.